„Zbadać i wyświetlić”. Centralna Żydowska Komisja Historyczna (1944–1947) - Haska, Agnieszka (Zagłada Żydów. Studia i Materiały, 2017)
In the studies published so far the Central Jewish Historical Commission (Centralna Żydowska Komisja Historyczna, CŻKH) has been treated as a prelude to the target operation of the Jewish Historical Institute. Little attention has been devoted to its organizational structure and general operation, with emphasis laid on collection of testimonies, securing archives, and publications. Meanwhile, the CŻKH objectives and tasks, including its main task, that is, documenting and talking about the lot of Polish Jews during World War II, were much broader than assumed. This article is a sketch of the CŻKH history – its activity, programmatic assumptions, and Holocaust research methodology.